The Effect of Agility Training on Underhand Passing Performance in Junior High School Volleyball Athletes - Adi Rohmat; Tedi Supriyadi; Ayi Suherman (Journal Coaching Education Sports, 2026)
This study aimed to determine the effect of agility training on underhand passing performance among junior high school volleyball athletes at the GIT Club and to identify the magnitude of its effect. This study employed a quantitative experimental method using a one-group pretest-posttest design. The sample consisted of 20 junior high school volleyball athletes selected through purposive sampling. The agility training program was conducted for 6 weeks with a frequency of 3 sessions per week, including shuttle runs, zig-zag runs, ladder drills, and cone drills. Data were collected using an underhand passing skill test administered before and after the intervention. The data were analyzed using homogeneity tests, paired sample t-tests, and the coefficient of determination (R-square) with the assistance of IBM SPSS Statistics software. The results showed a significant effect of agility training on underhand passing performance, with a significance value of 0.000 (p < 0.05). The mean pretest score increased from 62.45 to 81.30 in the posttest, with a mean difference of 18.85. The paired sample t-test revealed a t-value of 8.742, indicating a statistically significant improvement after the training program. Furthermore, the R-square value showed that agility training contributed 70.7% to the improvement in underhand passing performance. These findings indicate that agility training is an effective method for improving underhand passing skills in junior high school volleyball athletes.